Fabrication of surface-modified poly(3-aminobenzoic acid)/multiwalled carbon nanotubes composite thin films for hydrogen peroxide sensing - Chanyanuch Artitayakun (2018)
© 2017 Taylor & Francis Group, LLC. This work reports the fabrication of poly(3-aminobenzoic acid), (PABA)/multiwalled carbon nanotubes (MWNTs) composite thin film modified with layer-by-layer (LbL) self-assembled multilayers of cytochrome C (Cyt C) and poly(diallyldimethylammonium chloride) (PDADMAC) for hydrogen peroxide (H 2 O 2 ) sensing on indium tin oxide-coated glass substrate. An electropolymerized PABA/MWNTs composite thin film was employed for the covalent attachment of Cyt C. The subsequent multilayers of PDADMAC and Cyt C were then fabricated using LbL deposition technique. The fabricated film was characterized by UV-vis spectroscopy, Raman spectroscopy, SEM and AFM. The modified thin film was finally used for successive detection of H 2 O 2 at constant applied potential through an electrochemical method.